IDENTIFIKASI KLON JATI (Tectona grandis Linn F.) MENGGUNAKAN PENANDA SCAR (Seguence Characterized Amplified Region). - Vivi Yuskianti (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2009)
An easy, Cheap and acacurate identification method is needed to ensure the identity of teak clones used in planation. Molecular markers offer an alternative technique for clonal identivication . one such method is SCAR markers. Seventy teak clones of which 20 clones were produced by tissue cultures and claimed to be originated from the some parent. And 50 clones from buddings were used as materials. Analysis was conducted using 6 highly polymorphic SCAR primers. The results showed that 20 teakclones Originated from tissue cultures clustered into 3 groups, Whereas the rest 50 samples from buddings clustered into 4 groups. SCAR markers were able to differentiate the identity of these clones.These SCAR markers can applied to prove the claim abaout the identity of chones in the market and to ovoid labeling errors in the field for Vegetatively propagated plants.